Metal inclusion influence on mechanical behaviour of plates made of araldite - Draghici, Sorin; Petrescu, Horia Alexandru; Jiga, Gabriel; Vintilă, Sebastian; Hadar, Anton (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Due to the need for creating new, more efficient, materials for use in structures manufacturing, a high interest issue for researchers and engineers is to analyze the plastic or composite material defects and their influence over the mechanical behavior of the structures. Presented in this paper are the results of experimental analysis and its validation, made by finite element numerical analysis. The first part of the analysis process consisted in obtaining the reference values from plastic plates containing no metallic inclusions, which were analyzes both experimentally and numerically, by subjecting them to a flexural load. A numerical validation of the experimental model was obtained. Next, same kind of numerical and experimental analyses were performed, but this time plastic plates containing metallic inclusions were subjected to the same loads as before. In doing so, the study revealed the local and global influences of inclusions over the mechanical behavior of plastic plates.